2016
DOI: 10.1002/anie.201510029
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Temperature Solution Synthesis of Few‐Layer 1T ′‐MoTe2 Nanostructures Exhibiting Lattice Compression

Abstract: Molybdenum ditelluride, MoTe2 , is emerging as an important transition-metal dichalcogenide (TMD) material because of its favorable properties relative to other TMDs. The 1T ' polymorph of MoTe2 is particularly interesting because it is semimetallic with bands that overlap near the Fermi level, but semiconducting 2H-MoTe2 is more stable and therefore more accessible synthetically. Metastable 1T '-MoTe2 forms directly in solution at 300 °C as uniform colloidal nanostructures that consist of few-layer nanosheets… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(69 citation statements)
references
References 37 publications
3
65
0
1
Order By: Relevance
“…Clearly, the typical thickness of a single MoTe 2 flake was ≈2.1 nm, with a size of several square micrometers (Figure c). From the cross‐sectional HRTEM image in Figure S1 (Supporting Information), the interlayer spacing was measured to be 0.69 nm, very close to the reported value (0.7 nm), indicating that ultrathin MoTe 2 flakes have three layers. By contrast, the typical thickness of bulk MoTe 2 was greater than 300 nm (Figure S2, Supporting Information).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Clearly, the typical thickness of a single MoTe 2 flake was ≈2.1 nm, with a size of several square micrometers (Figure c). From the cross‐sectional HRTEM image in Figure S1 (Supporting Information), the interlayer spacing was measured to be 0.69 nm, very close to the reported value (0.7 nm), indicating that ultrathin MoTe 2 flakes have three layers. By contrast, the typical thickness of bulk MoTe 2 was greater than 300 nm (Figure S2, Supporting Information).…”
Section: Resultssupporting
confidence: 80%
“…First, ultrathin MoTe 2 layers were synthesized by chemical vapor deposition, followed by ultrasonic exfoliation ( Figure , for more details see Supporting Information) . Transmission electron microscopy (TEM) images were recorded to examine the morphology of the mechanically exfoliated MoTe 2 layers and Figure a shows a typical TEM image: Several aggregated ultrathin flakes were observed.…”
Section: Resultsmentioning
confidence: 99%
“…The polarization dependence also revealed that the totally symmetric Raman mode at ≈260 cm −1 is comprised of at least two peaks, although some simulations predict additional peaks. 44,49 These measurements help to clarify a discrepancy in the literature concerning the Raman scattering from 1T′ MoTe 2 as well as illustrate the changes in the crystal symmetry with layer parity. Finally, we demonstrate the relationship between the crystal axes and Raman polarization dependence, thereby enabling the identification of crystal orientation from Raman measurements alone.…”
mentioning
confidence: 76%
“…The properties of TMDs are closely associated with the polymorphism in crystal symmetry . In MoTe 2 , the room‐temperature stable phase is hexagonal 2H ( Figure a), which displays a bandgap of ≈1 eV, appealing for flexible and transparent optoelectronics devices . Through controllable conversion from 2H to the other semimetallic phases Tʹ (monoclinic, Figure b) and T d (orthorhombic, Figure c), the semiconducting to metallic transition can be realized, which helps achieve ohmic contact in heterojunctions and make broad applications including memory and phase‐change devices .…”
mentioning
confidence: 99%